2020
DOI: 10.3390/ma13030558
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Stabilized Oxides owning Fluorite Structure obtained by Hydrothermal Treatment

Abstract: Entropy-Stabilized Oxides (ESO) is a modern class of multicomponent advanced ceramic materials with attractive functional properties. Through a five-component oxide formulation, the configurational entropy is used to drive the phase stabilization over a reversible solid-state transformation from a multiphase to a single-phase state. In this paper, a new transition metal/rare earth entropy-stabilized oxide, with composition Ce0.2Zr0.2Y0.2Gd0.2La0.2O2−δ, was found after several investigations on alternative cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…The growing interest in the field of HEOs is illustrated by the numerous studies focusing on their different structural and functional aspects that have already been reported within the five years since their discovery. Currently, there are eight major classes of HEOs that can be categorized based on the crystallographic structures: rocksalt, 1,3,8,9 fluorite, [10][11][12][13][14][15] bixbyite, 10,12,16 perovskite (cubic, orthorhombic, rhombohedral), 5,[17][18][19] spinel, 20,21 pyrochlore, 7,[22][23][24] layered (Ruddlesden-Popper and delafossite) [25][26][27] and magnetoplumbite. 28,29 Likewise, a broad range of properties, such as electrochemical, 2,[30][31][32] optical, 11,[33][34][35] magnetic, 21,29,34,[36][37][38][39][40][41][42]…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in the field of HEOs is illustrated by the numerous studies focusing on their different structural and functional aspects that have already been reported within the five years since their discovery. Currently, there are eight major classes of HEOs that can be categorized based on the crystallographic structures: rocksalt, 1,3,8,9 fluorite, [10][11][12][13][14][15] bixbyite, 10,12,16 perovskite (cubic, orthorhombic, rhombohedral), 5,[17][18][19] spinel, 20,21 pyrochlore, 7,[22][23][24] layered (Ruddlesden-Popper and delafossite) [25][26][27] and magnetoplumbite. 28,29 Likewise, a broad range of properties, such as electrochemical, 2,[30][31][32] optical, 11,[33][34][35] magnetic, 21,29,34,[36][37][38][39][40][41][42]…”
Section: Introductionmentioning
confidence: 99%
“…Together with Gd-and Nd-doped ceria, Sm-doped ceria is one of the most effective systems of ionic conductivity [1]. Ionic conductivity is strictly related to structural and microstructural issues, and this is the reason why so many papers in recent years have been devoted to the crystallographic properties of this material, even in the light of the non-negligible effects of extrinsic factors (e.g., thermal treatments) on the stability of the various oxide phases [15,16]. A particular attention has been paid to defect aggregations [3,[17][18][19][20][21], since ionic conductivity in doped ceria occurs through the hopping of oxygen ions towards the vacancies (V .. O ) created for charge compensation when Ce 4+ is partially substituted by RE 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that urea can be used as a precipitator in hydrothermal treatment to construct samples of different morphologies [31][32][33][34]. In this work, three-dimensional agglomerated structures from unclosed to blocking sphere-shaped microstructure for NCM 111 were designed by controlling the contents of urea to get excellent electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%